PRINSIP KESANTUNAN TUTURAN DALAM BAHASA JAWA: prinsip kesantunan - Kinasih Yuliastuti; Bayu Indrayanto; Ike Anisa (LPPM Universitas Widya Dharma, 2024)
The politeness principle speech act in Javanese is the use of Javanese that occurs in Javanese society. In using Javanese, speakers must understand speech act, however, errors often occur in the use of the lexicon. This cannot be completely blamed, because it can occur due to several factors, for example: the speaker's lack of knowledge about the concept of speech act in Javanese, the speaker's lack of mastery of Javanese vocabulary. Usually this is experienced by immigrants who have lived outside Java for a long time or by young people (especially children) who do not yet understand and master uploading. Politeness in language reflects a person's refined manners and noble character by not hurting feelings and giving choices to other people. The principle of language politeness means an attitude of concern for the face or face, both of the speaker and of the interlocutor.